Preliminary phytochemical investigation of Combretum albidum G. Don; An ignored medicinally important liana. - N, Bokhad M; P, Rothe S (Journal of Experimental Sciences, 2012)
Day by day faith of people on herbal medicine is increases due to the side effect of synthetic drugs, and results into people started looking back to the traditional knowledge of plant for their health care in day to day life. Certain local practitioner, traditional healers uses the decoction of the fruit of Combretum albidum G. Don in the treatment of diarrhoea and dysentery, stem barks used in jaundice. So the present study deals with preliminary phytochemical analysis of stem, leaf, flower and fruit using six different solvent. It needful helps for the scientific documentation and standardization of row plant material used in medicine and its worldwide acceptance.